Sugars and proteins: New strategies in synthetic biology - Davis, B (2009)
The development of novel methodology for bond-forming processes that are compatible with biomolecules allows the assembly, alteration, or modification of proteins. Such synthetic proteins allow precise insight and investigation of function in a manner that has the potential for almost unlimited diversity. © 2009 IUPAC.